Dynamics, Statics, and the Stationary State - Samuelson, Paul A. (The Review of Economics and Statistics, 1943)
U NTIL now, much of dynamical economic analysis has been concerned with the business cycle. This may seem so natural as to be hardly worthy of explicit comment. Nevertheless, it was not inevitable; and if in the future the business cycle, as we have known it, should undergo extreme modifications, a need for dynamical analysis in connection with many economic problems would still exist. Thus, we should still need a theory of the path by which a given market approaches its equilibrium position, not for sake of the theory alone, but for the information that such knowledge throws upon the direction of displacement of the new equilibrium position as well.' In comparatively recent times, significant advances have been made in analytical dynamics. A rigorous differentiation between statics and stationariness, between dynamics and history, is now possible. The present essay attempts, first, to elucidate the nature of these concepts and to contrast them with some other prevalent usages of the terms; and, second, by means of the concepts to go back to analyze the very important notion of the circular flowo. In doing so, I am not attempting to improve upon what I consider a logically consistent argument, but rather am endeavoring to amplify the discussion at critical points where confusion has arisen.